Community Participation Makes Equal Welfare - Noya, Josephus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community Welfare is a concept that shows the government's responsibility to provide social protection to all its citizens. It requires active participation from the community to achieve this. This article aims to discuss the importance of active community participation in realizing a welfare state, along with the challenges and obstacles. This research is descriptive research that describes the social behavior of the community which is related to the active participation of the community in realizing a welfare state. The results of this research are that there are several obstacles in implementing community participation, such as the lack of public understanding of the importance of participation, differences in views and interests, as well as limited resources and support from the government. The government needs to strengthen coordination and collaboration with the community in planning and implementing welfare programs as well as ensuring transparency and accountability in managing public resources and building an effective monitoring system.